2011
DOI: 10.1534/genetics.111.131839
|View full text |Cite
|
Sign up to set email alerts
|

Rapid GAL Gene Switch of Saccharomyces cerevisiae Depends on Nuclear Gal3, Not Nucleocytoplasmic Trafficking of Gal3 and Gal80

Abstract: The yeast transcriptional activator Gal4 localizes to UAS GAL sites even in the absence of galactose but cannot activate transcription due to an association with the Gal80 protein. By 4 min after galactose addition, Gal4-activated gene transcription ensues. It is well established that this rapid induction arises through a galactose-triggered association between the Gal80 and Gal3 proteins that decreases the association of Gal80 and Gal4. How this happens mechanistically remains unclear. Strikingly different hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 65 publications
1
26
0
Order By: Relevance
“…Our results are consistent with recently published data suggesting that under inducing conditions, Gal3p transiently associates with a Gal4p-Gal80p complex (5). We go on to show, however, that the dissipation of Gal3p is coincident with the recruitment of the galactokinase (Gal1p) to Gal4p (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with recently published data suggesting that under inducing conditions, Gal3p transiently associates with a Gal4p-Gal80p complex (5). We go on to show, however, that the dissipation of Gal3p is coincident with the recruitment of the galactokinase (Gal1p) to Gal4p (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Chromatin immunoprecipitation (ChIP) experiments (19) and pulldown assays (24) both suggest that the Gal4p-Gal80p complex is somewhat weakened (although perhaps not completely dissociated) when cells are grown in the presence of galactose. Recently published data, however, suggest that nuclear-cytoplasmic shuttling of Gal80p is not required for the expression of the GAL genes and that the induction of GAL gene expression can occur with both Gal80p and Gal3p in the nucleus (5).…”
mentioning
confidence: 98%
“…It is still unclear, however, whether the three proteins would colocalize-whether Gal3p ever enters the nucleus, as discussed above. A recent study suggested that a tripartite complex might form very transiently in the nucleus (Egriboz et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other reports claim that Gal3p does enter the nucleus in the presence of galactose, and induction occurs through the association of a tripartite complex formed between Gal4p, Gal80p, and Gal3p (Platt and Reece 1998;Wightman et al 2008;Jiang et al 2009). Recently, Hopper and colleagues (Egriboz et al 2011) suggested that there is sufficient Gal3p in the nucleus prior to galactose induction to account for the rapid induction kinetics.…”
mentioning
confidence: 99%
“…In the GAL network, the galactose signal propagates through a four-stage signalling cascade 4,9,11,12 . The galactose transporter Gal2p imports extracellular galactose into the cell, and intracellular galactose binds to and activates the signal transducer Gal3p.…”
mentioning
confidence: 99%